Memantine associated with parkisonism in a patient with Alzheimer's disease: A case study and the review of the literature - Štuhec, Matej (Anali PAZU, 2022)
The positive effect of memantine on parkinsonism has been reported widely, but there have not been reports in the literature of parkinsonism, tremor and bradykinesis, induced by memantine, in an Alzheimer's patient, who did not have Parkinson's disease or a history of antipsychotic agents. In this case study, we report parkinsonism, tremor and night bradykinesis induced by memantine use (5 mg daily) in a 83-year-old Slovenian female patient. After memantine discontinuation, suggested by a clinical pharmacist specialist, and switching to donepezil 5 mg, the adverse drug reactions disappeared the next day. This case study may serve to help clinicians and clinical pharmacists distinguish memantine-induced parkinsonism from more serious conditions.
Keywords: parkinsonism; adverse event; literature review; Alzheimer's disease; clinical pharmacy